Effects of an essential amino acid mixture on behavioral and psychological symptoms of dementia and executive function in patients with Alzheimer's disease: A double‐blind, randomized, placebo‐controlled exploratory clinical trial. (5th August 2022) - Takada, Michihiro; Tanaka, Shin; Tanaka, Koh; Tsukie, Tamao; Tsukamoto‐Yasui, Masako; Suzuki, Katsuya; Noguchi, Yasushi; Imaizumi, Akira; Ishii, Makoto; Ikeuchi, Takeshi
Abstract: Background: The increasing number of dementia patients has become a global social problem. Amino acids are known to be used as precursors of neurotransmitters in the brain. Amino acid mixtures as a supplement may be used as a solution to Alzheimer's symptoms. This exploratory study evaluated the efficacy and safety of a mixture containing nine essential amino acids on behavioral and psychological symptoms of dementia (BPSD) and cognitive function in patients with Alzheimer's disease (AD). Design: We conducted a double‐blind, randomized, placebo‐controlled trial to evaluate the intervention effects of nine essential amino acid mixture for 28 days. A total of 36 patients with AD were enrolled in Japan. BPSD and cognitive function were evaluated by the Neuropsychiatric Inventory‐12 item (NPI‐12; the primary endpoint), Mini‐Mental State Examination (MMSE), Trail Making Test A (TMT‐A), Trail Making Test B (TMT‐B), Frontal Assessment Battery (FAB), and Clinical Dementia Rating Scale (CDR). Results: Compared with placebo, the amino acid mixture did not improve NPI‐12, MMSE, TMT‐A and B or CDR scores. However, the analysis of covariance revealed improved FAB scores in the amino acid mixture group as a secondary endpoint. There were four subjects with adverse events in each group. Conclusions: Our results did not show a beneficial effect of the mixture containing nine essential amino acids on BPSD as a primary endpoint; however, it may improve executive function in patients with AD. Key points: A double‐blind randomized placebo‐controlled trial was conducted to evaluate the effect of the mixture containing nine essential amino acids in patients with Alzheimer's disease. Intervention with amino acids mixture did not improve the behavioral and psychological symptoms of dementia. It was suggested that executive function may be improved by intervention of amino acid mixture.